A Formula for the Reliability of a d-Dimensional Consecutive-k-out-of-n:F System. (13th July 2015) - Cowell, Simon
Abstract : We derive a formula for the reliability of ad -dimensional consecutive-k -out-of-n :F system, that is, a formula for the probability that ann 1 × ⋯ × n d array whose entries are (independently of each other) 0 with probabilityp and 1 with probabilityq = 1 - p does not include a contiguouss 1 × ⋯ × s d subarray whose every entry is 1.